1996
DOI: 10.1016/s0092-8674(00)80152-x
|View full text |Cite
|
Sign up to set email alerts
|

The Product of par-4, a Gene Induced during Apoptosis, Interacts Selectively with the Atypical Isoforms of Protein Kinase C

Abstract: The atypical PKCs are involved in a number of important cellular functions, including cell proliferation. We report here that the product of the par-4 gene specifically interacts with the regulatory domains of zeta PKC and lambda/LPKC, which dramatically inhibits their enzymatic activity. This is particularly challenging, because expression of par-4 has been shown to correlate with growth inhibition and apoptosis. Results are shown here demonstrating that the expression of par-4 in NIH-3T3 cells induces morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
377
1
1

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 358 publications
(395 citation statements)
references
References 48 publications
15
377
1
1
Order By: Relevance
“…Interestingly, Par-4 was also found as interaction partner of PKC isoforms x and l/i using a similar twohybrid approach (Diaz-Meco et al, 1996). This study showed that Par-4 speci®cally inhibits PKC isoforms x and l/i but not others, thereby interrupting signaling to AP1 and inducing apoptosis (Berra et al, 1997).…”
Section: The Leucine Zipper As Interaction Domain In Transcription Famentioning
confidence: 66%
See 3 more Smart Citations
“…Interestingly, Par-4 was also found as interaction partner of PKC isoforms x and l/i using a similar twohybrid approach (Diaz-Meco et al, 1996). This study showed that Par-4 speci®cally inhibits PKC isoforms x and l/i but not others, thereby interrupting signaling to AP1 and inducing apoptosis (Berra et al, 1997).…”
Section: The Leucine Zipper As Interaction Domain In Transcription Famentioning
confidence: 66%
“…Par-4 (prostate apoptosis response gene 4) was originally identi®ed as a response gene induced upon induction of apoptosis in prostate carcinoma cells (Sells et al, 1994), and later on as interaction partner of transcription factor WT1, the Wilm's tumor gene product (Johnstone et al, 1996) and of PKC isoforms l/i and z (Diaz-Meco et al, 1996). Par-4 contains a leucine zipper which mediates its interaction with the zinc ®ngers of WT1 and PKC l/i/z.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that protein kinase Cg binds ceramide at its CI domain by a mechanism analogous to diacylglycerol binding by typical PKCs. Atypical CI domains of protein kinase C< and CL have also been implicated in protein-protein interactions (Diaz-Meco et al, 1996a, 1996b. Human protein kinase C p (known as protein kinase D in mouse) contains a catalytic domain which is more similar to Dicfyosteliurn myosin light-chain kinase than to other protein kinase Cs, and was initially classified as an atypical isozyme.…”
mentioning
confidence: 99%